Т.ҚАЙЫПБЕРГЕНОВТЫҢ ДРАМАЛЫҚ ШЫҒАРМАЛАРЫНЫҢ СЮЖЕТЛИК ӨЗГЕШЕЛИГИ - Жәримбетов, Қ.; Палымбетова, М. (SCIENCE and SOCIETY, 2019)
The article is devoted to the study of the plot-compositional structure of the tragedy “Aydos baba (The head evaluated to thousand gold coins)” by T.Kaipbergenov. The author presents his ideas and points of view about the historical personality of Aydos biy.